HCI in mobility, transport, and automotive systems : driving behavior, urban and smart mobility : second International Conference, MobiTAS 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings.: driving behavior, urban and smart mobility : second International Conference, MobiTAS 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings. Part II (2020) - Unknown
No abstract available